Voiding trial outcome following pelvic floor repair without incontinence procedures. Issue 8 (August 2016) - Wang, Rui; Won, Sara; Haviland, Miriam; Von Bargen, Emily; Hacker, Michele; Li, Janet; Lefevre, Roger
Abstract Introduction and hypothesis Our aim was to identify predictors of postoperative voiding trial failure among patients who had a pelvic floor repair without a concurrent incontinence procedure in order to identify low-risk patients in whom postoperative voiding trials may be modified. Methods We conducted a retrospective cohort study of women who underwent pelvic floor repair without concurrent incontinence procedures at two institutions from 1 November 2011 through 13 October 2013 after abstracting demographic and clinical data from medical records. The primary outcome was postoperative retrograde voiding trial failure. We used modified Poisson regression to calculate the risk ratio (RR) and 95 % confidence interval (CI). Results Of the 371 women who met eligibility criteria, 294 (79.2 %) had complete data on the variables of interest. Forty nine (16.7 %) failed the trial, and those women were less likely to be white (p = 0.04), more likely to have had an anterior colporrhaphy (p = 0.001), and more likely to have had a preoperative postvoid residual (PVR) ≥150 ml (p = 0.001). After adjusting for race, women were more likely to fail their voiding trial if they had a preoperative PVR of ≥150 ml (RR: 1.9; 95 % CI: 1.1–3.2); institution also was associated with voiding trial failure (RR: 3.0; 95 % CI: 1.6–5.4). Conclusions Among our cohort, postoperative voiding trial failure was associated with a PVR of ≥150 ml and institution at which the surgery was performed.